The Influence of Knowledge, Motivation and Workload on Implementation of Medical Compliance in SIRS - Muh. Tan'iem Nawawi; Andry Andry; Kemala Rita Wahidi (Jurnal Health Sains, 2023)
Based on the Law of the Republic of Indonesia Number 44 of 2009 concerning Hospitals Article 32 it is stated that every Hospitals are required to record and report on all Hospital management activities in the form of a Hospital Management Information System. The effect of knowledge, motivation and workload in the implementation of SIRS with medical personnel compliance as an intervening variable at the Kemayoran Athlete's Wisma RSDC. This study uses quantitative analysis using a cross sectional. This research was conducted in December-January 2021 with 161 samples, the sampling technique was random sampling. Data analysis using univariate and bivariate with test chi-square with p < 0.05. The results showed that there was a significant relationship between knowledge and SIRS compliance (P Value = 0.000), Motivation (P Value = 0.000), Workload (P Value = 0.000). The author recommends evaluating several aspects such as networking, system requirements development, human resource development to be reviewed and the addition of a personnel information subsystem to the SIRS service.